1992
DOI: 10.1029/92gl00083
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for marine production of isoprene

Abstract: New data obtained in the Mediterranean Sea and Pacific Ocean show that isoprene could be produced in sea water by biological processes, leading to concentrations in the ppb range (10−9 liter of gas per liter of water). Taking into account Henry's constant for isoprene in water and the very low concentrations measured in the marine atmosphere, the superficial sea water is supersaturated in isoprene by one or two orders of magnitude. From these observations, an oceanic flux of the order of 1.2 Mt per year of iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
178
2
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(194 citation statements)
references
References 14 publications
12
178
2
2
Order By: Relevance
“…Recent estimates for oceanic isoprene emissions range from 0.089 (Erickson and Hernandez, 2013) 0.11 Tg (C) a −1 (Palmer and Shaw, 2005), much lower than previous estimates (Bonsang et al, 1992). Besides their low contribution to global totals, oceanic isoprene emissions are the main local isoprene source, in particular in the remote ocean marine boundary layer.…”
Section: Ocean-to-atmosphere Fluxesmentioning
confidence: 65%
“…Recent estimates for oceanic isoprene emissions range from 0.089 (Erickson and Hernandez, 2013) 0.11 Tg (C) a −1 (Palmer and Shaw, 2005), much lower than previous estimates (Bonsang et al, 1992). Besides their low contribution to global totals, oceanic isoprene emissions are the main local isoprene source, in particular in the remote ocean marine boundary layer.…”
Section: Ocean-to-atmosphere Fluxesmentioning
confidence: 65%
“…The numbers on the peaks refer to the identified compounds reported in Table 2 Table 2, p-ocimene accounted for 37% of the total monoterpenes and was the dominant measured monoterpene in the emission of D. tertiolecta. Since we have employed a β-cyclodextrin capillary separation column, the enantiomers of Since terrestrial vegetation is known to emit both isoprene and monoterpenes, [34] and it has been established that marine phytoplankton do emit isoprene, [12,17] the emission of monoterpenes from phytoplankton cannot be entirely unexpected. It is worth considering that terpenes are common metabolites in marine plants and their formation by the condensation of isopentenyl pyrophosphate units is, in this regard, comparable to terrestrial metabolism.…”
Section: Emission Of Monoterpenes From Phytoplanktonmentioning
confidence: 99%
“…The main exception is dimethyl sulfide (DMS), which is known to be produced biogenically in the ocean [8,9] and yields the inorganic aerosol component sulfate upon complete oxidation in the atmosphere. [10,11] Isoprene, the strongest terrestrial biogenic emission, has also been observed as an oceanic emission [12] and in laboratory based studies of plankton. [13][14][15][16][17] Furthermore, it has also been shown to form aerosols over the tropical rainforest, [18] and more controversially suggested as the cause of cloud droplet radius changes in clouds that form directly over phytoplankton blooms.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Some organic trace gases, which are known to be emitted from the ocean (e.g. isoprene [3] ), exhibited significantly elevated mixing ratios over the phytoplankton bloom regions. Nonetheless the trace gas composition of the marine boundary layer of the remote Southern…”
Section: Introductionmentioning
confidence: 99%